Evaluation of forest structure, composition of commercial species, stand growth rate and volume among chronosequence stand after logging in Borneo, Sarawak - Diway, Bibian; Ling, Chea Yiing; James, Geoffery; Waseem Razzaq Khan, .; Kueh, Roland Jui Heng; Anak Layang, Bryan Pastdy (Forestry Department Peninsular Malaysia, 2022)
The study on growth rate and yield are some of the parameters in forest dynamics. The information on these aspects can help to infer better future timber production in a managed tropical rainforest helping in achieving sustainable forest management policy. However, information on these aspects of tropical rainforest in Malaysia is scarce, especially in Sarawak. This study was carried out to evaluate the forest stand structure, stand growth, and yield at Forest Management Unit (FMU), Bintulu, Sarawak among chronosequence stand after logging. Five study plots, 16 (15 years after logging), 17 (undisturbed), 18 (11 years after logging), 19 (21 years after logging) and 20 (7 years after logging) were established. Tree diameter at breast height (DBH) ≥ 10 cm and height measurements were enumerated and recorded. The study showed that non-Dipterocarp species dominated in all plots in terms of the number of trees. Dipterocarpaceae family dominated the understorey, main canopy, and emergent layers. Plot 17 shows the lowest growth rate of 0.28 cm year-1 while plot 18 and 19 have the highest growth rate of 0.59 cm year-1 respectively. Dipterocarp groupings of commercial and non-commercial showed higher growth compared to non-Dipterocarp tree species. Plot 17 and 18 showed the highest and lowest mean volume of 277.96 m 3 /ha and 150.86 m 3 /ha. Commercial Non-Dipterocarp group gave higher tree volume yield than the other groupings. This study suggested that there are differences in terms of forest structure, growth rate and yield performance based on different years after logging. This indicates that logging activities affects the condition of the forest stand and longer monitoring of the sites should be applied to further understand these aspects of forest dynamics.